Toward a theory of mechanochemistry: Simple models from the very beginnings. Issue 23 (3rd October 2018) - Quapp, Wolfgang; Bofill, Josep Maria; Ribas‐Ariño, Jordi
Abstract: A core idea in the context of mechanochemistry is that applying an external tensile force along a reaction coordinate should enhance the chemical reaction of interest. Here, we analyze perturbed generic molecular structures: schematic models of triatomics, ABC, and tetraatomics, AABB. They are used to demonstrate that pulling does usually not use the "reaction coordinate, " but opens new reaction pathways. Within development of these models we use the concept of Newton trajectories for a theory of mechanochemistry. However, we find cases where the theory of Newton trajectories is not applicable. For all cases, we define the curve of force‐displaced stationary points, and we discuss the importance of barrier breakdown points and valley‐ridge inflection points. The examples use Morse potentials for bonds and simple angle functions and are demonstrated by assumed real values for the potential parameters. On the basis of the systematic study of some generic models we explain a set of already observed experimental mechanochemical phenomena in specific molecular systems and we apply the results to the strength of chemical bonds. Abstract : A core idea in the context of mechanochemistry is that applying an external tensile force along a reaction coordinate should enhance the chemical reaction of interest. Triatomic models are used to demonstrate that pulling does usually not use the "reaction coordinate, " but instead opens completely new reaction pathways. The concept of Newton trajectories is used to develop a theory of mechanochemistry.